Effects of intermittent IL-2 alone or with peri-cycle antiretroviral therapy in early HIV infection: the STALWART study. - Jorge A Tavel; INSIGHT STALWART Study Group; Abdel Babiker; Lawrence Fox; Daniela Gey; Gustavo Lopardo; Norman Markowitz; Nicholas Paton; Deborah Wentworth; Nicole Wyman (PLoS ONE)
Background The Study of Aldesleukin with and without antiretroviral therapy (STALWART) evaluated whether intermittent interleukin-2 (IL-2) alone or with antiretroviral therapy (ART) around IL-2 cycles increased CD4(+) counts compared to no therapy. Methodology Participants not on continuous ART with > or = 300 CD4(+) cells/mm(3) were randomized to: no treatment; IL-2 for 5 consecutive days every 8 weeks for 3 cycles; or the same IL-2 regimen with 10 days of ART administered around each IL-2 cycle. CD4(+) counts, HIV RNA, and HIV progression events were collected monthly. Principal findings A total of 267 participants were randomized. At week 32, the mean CD4(+) count was 134 cells greater in the IL-2 alone group (p<0.001), and 133 cells greater in the IL-2 plus ART group (p<0.001) compared to the no therapy group. Twelve participants in the IL-2 groups compared to 1 participant in the group assigned to no therapy experienced an opportunistic event or died (HR 5.84, CI: 0.59 to 43.57; p = 0.009). Conclusions IL-2 alone or with peri-cycle HAART increases CD4(+) counts but was associated with a greater number of opportunistic events or deaths compared to no therapy. These results call into question the immunoprotective significance of IL-2-induced CD4(+) cells. Trial registration ClinicalTrials.gov NCT00110812.